Incidencia de la remuneración mínima vital en la gestión financiera de las mypes del sector comercial del distrito de Trujillo - Ruiz Campos, Miluska Sharon (2017)
The present research was carried out with the objective of analyzing the impact of the increase in minimum vital remuneration in the financial management of Micro and Small Business Enterprises before and after it varies, as well as the financial situation presented by Which can determine the financial management that has been and is managing this company. To carry out this research was sampled one hundred thirty micro companies of district of Trujillo, To which, through the survey that was the instrument used, it was possible to obtain real information that after the respective financial analysis shows that the liquidity as well as the profits of these companies have been affected. But with the right strategies and policies can minimize contingencies that may be negative for the company. It is also important to note that the design of this research is non-experimental. This is why it is concluded that the increase in the minimum remuneration has a significant impact within these companies and that it is necessary that an expenditure planning is done, that addressed in the appropriate way could maintain the liquidity and likewise increase the utility , which is properly targeted, can be maintained, since the increase in the minimum wage does not benefit the microentrepreneur; generating a great obstacle to their development and permanence in the market, other companies with more time and more important in the market are still difficult, but they can continue to be in force. This is observed in the results that the companies studied present.